The role of pedagogical differentiation in reducing emotional disturbances and its effects on the learning of students in inclusive primary classes - Younes BOUSMAHA; Lahcen SEDDIK; M’bark BOUALI (International Journal of Scientific Research and Innovative Studies, 2025)
This study explored the impact of adopting pedagogical differentiation on the reduction of emotional disorders among primary school students with disabilities, focusing specifically on anxiety, depressive symptoms, and behavioral difficulties. The findings revealed a significant decrease in these symptoms after the implementation of differentiated strategies, confirming the initial hypotheses. The results suggest that inclusive practices, through instructional adaptation and the removal of learning barriers, create a supportive and safe environment where students feel valued and engaged. This emotional improvement enhanced self-regulation, reduced distress, and promoted more positive classroom behaviors. These outcomes are consistent with existing literature, including the works of Florian and Black-Hawkins (2011), Merrell and Gueldner (2020), and Meirieu (2018), which emphasize the positive effects of pedagogical differentiation on emotional well-being and academic engagement. The study highlights the importance of teacher training, the provision of adapted pedagogical resources, and the integration of differentiation into educational policies to ensure equity and sustainability. Although limited by sample size and duration of intervention, the study provides promising insights for future research and practice. Keywords : Pedagogical differentiation, inclusive education, emotional disorders, students with disabilities, primary education. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/457